Developing service climate in local vs. foreign firms in smaller Asian emerging markets: a resource-based and social exchange perspective. Issue 4 (21st February 2017) - Hoang, Hung Trong; Rao Hill, Sally; Freeman, Susan; Lu, Vinh Nhat; Imrie, Brian C.
Abstract: While research on drivers of service climate has focused on organisational resources and human resource practices such as training, employee autonomy and inter-departmental support, how these resources interrelate and influence service climate has not been examined, especially in the context of smaller Asian emerging market. Drawing on the resource-based view and its extension on dynamic capability, and social exchange theory, this qualitative study investigates how local and foreign firms in smaller Asian emerging markets create a favourable service climate. Our findings suggest three inter-related groups of factors that influence service climate, namely firm-based, market-based and culture-based drivers. Notably, foreign service firms perform better than their local counterparts in several firm-based drivers (e.g. service-oriented human resource management practices, work facilitation resources). Our study proposes a conceptual framework that integrates inter-relationships of organisational resource-based factors and explains how internal and external factors drive service climate in firms in smaller Asian emerging markets.